2018
DOI: 10.1007/s10815-018-1324-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for inadequate response to ovarian stimulation in assisted reproduction cycles: systematic review

Abstract: Purpose Controlled ovarian stimulation is a fundamental part of a successful assisted reproduction treatment, and recognizing patients at risk of a poor response allows the development of targeted research to propose new treatment strategies for this specific group. The objective of this systematic review was to determine risk factors for poor ovarian response (POR) to controlled stimulation in assisted reproduction cycles described in the literature. Methods The primary databases MEDLINE, Cochrane, LILACS, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 92 publications
0
3
1
1
Order By: Relevance
“…Our results of clinical characteristics in endometrial biopsy between the groups less than 90 days and the time between 90 and 180 days did not show differences between the groups with the characteristics of mother's age, BMI, type of endometrial preparation, natural cycle, and progesterone supplementation. Our results are not in agreement with some clinical characteristics in the literature, such as maternal age, that the older the mother, the lower the pregnancy success rate and the higher the BMI, and hence the lower the pregnancy success rate 9,14 . Another study concluded that infertility duration, endometrial thickness, and number of embryos transferred might affect the live birth rate after frozen embryo transfer among young women 15 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results of clinical characteristics in endometrial biopsy between the groups less than 90 days and the time between 90 and 180 days did not show differences between the groups with the characteristics of mother's age, BMI, type of endometrial preparation, natural cycle, and progesterone supplementation. Our results are not in agreement with some clinical characteristics in the literature, such as maternal age, that the older the mother, the lower the pregnancy success rate and the higher the BMI, and hence the lower the pregnancy success rate 9,14 . Another study concluded that infertility duration, endometrial thickness, and number of embryos transferred might affect the live birth rate after frozen embryo transfer among young women 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our results may enforce this idea by indicating that early embryo transfer (<90 days) is better than late embryo transfer for pregnancy success. Amaral et al 9 reviewed the influencing factors of pregnancy loss and survival probability of clinical pregnancies through ART and some factors such as maternal age, controlled ovarian hyperstimulation protocol, cycle type, and serum hCG level 14 days after transfer. Bashiri et al 10 , who reviewed on recurrent implantation failure (RIF), suggested a new initial step in approach to patients with RIF, as in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, environmental endocrine disruptors, tobacco, genetic mutations, endometriomas, ovarian surgery, chemotherapy, and short menstrual cycles are factors that affect the stimulation process in assisted reproduction cycles. [26] In this study, we excluded samples with a history of endometriomas, ovarian surgeries, and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Na publicação original menciona-se ainda a inclusão de pacientes com fatores de risco para má-resposta além da idade como um dos critérios diagnósticos, porém não se discrimina quais. Estudo do nosso grupo demonstrou que são diversos os fatores de risco para má resposta, tais como exposição prévia à quimioterapia, ciclos menstruais curtos, mutações genéticas, tabagismo, exposição a químicos ambientais, endometriomas e cirurgias ovarianas prévias [23]. Um critério diagnóstico ideal deve ser simples, claro e reprodutível, de tal modo que a determinação de exatamente quais fatores de risco serão adotados é importante para tornar a população inclusa no critério diagnóstico mais homogênea.…”
Section: Lista De Abreviaturas Símbolos E Siglasunclassified